The Sopranos: Coming in at the End - Marques, Maria João (VIA PANORAMICA: Revista de Estudos Anglo-Americanos / A Journal of Anglo-American Studies, 2017)
The Sopranos (1999-2007), created by David Chase for HBO, set the tone for what the series of the 21st century would be about: a man’s struggle for power and control over others and himself amid a desolate reality. A self-referential series deconstructing mobster clichés and the role of the modern hero while nostalgically plunging into the depths of the old-time gangster, The Sopranos turned its critical focus to the present time of the United States. Introducing the first bad leading man in a television series whose tragic nature challenged the very notions of hero, villain, and television storytelling, this series created a rupture in the hero paradigm. Under a self-reflection that satirically revered the criminal heroes of the past, The Sopranos ultimately questioned the perpetuation of a myth – the hero figure, either cowboy or gangster